Is this really kneaded? Identifying and eliminating potentially harmful forms of workplace control - Guido Friebel; Matthias Heinz; Mitchell Hoffman; Tobias Kretschmer; Nick Zubanov (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
In a large German bakery chain, many workers report negative perceptions of monitoring via checklists. We survey workers and managers about the value and time costs to all in-store checklists, leading the firm to randomly remove two of the most perceivedly time-consuming and low-value checklists in half of stores. Sales increase and store manager attrition substantially decreases, and this occurs without a rise in measurable workplace problems. Before random assignment, regional managers predict whether the treatment would be effective for each store they oversee. Ex post, beneficial effects of checklist removal are fully concentrated in stores where regional managers predict the treatment will be effective, reflecting substantial heterogeneity in returns that is well-understood by these upper managers. Effects of checklist removal do not appear to come from workers having more time for production, but rather due to improvements in employee trust and commitment. Following the RCT, the firm implemented firmwide reductions in monitoring, eliminating a checklist regarded as demeaning, but keeping a checklist that helps coordinate production.
Keywords: 330; Monitoring; checklists; respect; time use